Ovine leukocyte microparticles generated by the CentriMag ventricular assist device in vitro - Owen Bodger (Artificial Organs, 2018)
Ventricular assist devices (VADs) are a life-saving form of mechanical circulatory support in heart failure patients. However, VADs have not yet reached their full potential due to the associated side effects (thrombosis, bleeding, infection) related to the activation and damage of blood cells and proteins caused by mechanical stress and foreign materials. Studies of the effects of VADs on leukocytes are limited, yet leukocyte activation and damage including microparticle generation can influence both thrombosis and infection rates. Therefore, the aim was to develop a multicolour flow cytometry assessment of leukocyte microparticles (LMPs) using ovine blood and the CentriMag VAD as a model for shear stress. Ovine blood was pumped for 6 hours in the CentriMag and regular samples analysed for haemolysis, complete blood counts and leukocyte microparticles by flow cytometry during three different pump operating conditions (low flow, standard, high speed). The high speed condition caused significant increases in plasma-free haemoglobin; decreases in total leukocytes, granulocytes, monocytes and platelets; increases in CD45+ LMPs as well as two novel LMP populations: CD11bbright/HLA-DR- and CD11bdull/HLA-DR+, both of which were CD14-/CD21-. CD11bbright/HLA-DR- LMPs appeared to respond to an increase in shear magnitude whereas the CD11bdull/HLA-DR+ LMPs significantly increased in all pumping conditions. We propose that these two populations are released from granulocytes and T cells, respectively, but further research is needed to better characterise these two populations.